Medo e sofrimento social: uma análise das narrativas de policiais militares em atendimento clínico - Sales, Larissa Jucá de Moraes (2013)
This research builds up from the subjective perspective of Military Police Officers in regards to their working activity. The intention is to understand how to establish an explanatory logic featuring work as a part of the subject’s illness – as it is revealed by these social actors, characterized by the discourse of medicalization as “subjects in crisis” and “diagnosed” as carriers of psychological diseases. For such an enterprise, an intensive fieldwork research of seven months was conducted inside one of the military institution’s treatment unit in Fortaleza, Brazil: the Corporation’s Biopsychosocial Center. Within this interactional context, the access to these subjects and a part of their treatments were selected as the focus. Following these subjects’ symbolic categories, they attribute a share of their illness to two kinds of problems perceived as constituents of their work routine. First, as problems directly affecting the individual’s body, such as unhealthy working conditions, lack of security equipment leaving the subject vulnerable to the unpredictable, and the exhausting work schedules, with long hours standing on foot under the sun, among others. The second problem is based on the symbolic violence that directly affects an individual’s mind, inflicting an invisible pain capable of generating suffering, such as moral harassment, humiliation, abuse of authority and covert punishment. The second problem is the most recurring in these subjects’ narratives. For these social agents, such problems affect their bodies in the form of illnesses, which reverberate as professional pressure directly influencing their ways of being in society. For some of them, these illnesses are also used for justifying acts of violence. An ethnographic experience was carried out as a methodological approach inside this treatment Center, from which the life trajectories of three military police officers and fragments of life stories were selected to feature as clarifying sources of this problem. The justifications are initiated by the aforementioned conditions conducive to illness, passing to therapeutic monitoring and concluded by adherence to religious groups as a possible path of cure. Another case to be highlighted is one of tragic outcome, which led to suicide. In this perspective, categories of humiliation, suffering and fear are mobilized by the individuals and their colleagues in uniform to explain their dramas. Ultimately, we aim to promote comprehension of how these subjects understand their work considering this condition.